The in vitro effect of delta-9-tetrahydrocannabinol and cannabidiol on whole blood viscosity, elasticity and membrane integrity - Tameika R. James; Andrea A. Richards; Dwight A. Lowe; Walton A. Reid; Charah T. Watson; Dagogo J. Pepple (BMC, 2022)
Abstract Background The main biological activities of cannabis are due to the presence of several compounds known as cannabinoids. Delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are two of the main cannabinoids. Studies have shown that the effects of THC can be modulated by CBD. Objective This study aims to look at the effect of different concentrations of THC and CBD separately and in combination, on blood viscosity, elasticity and membrane integrity. Methods Blood samples were collected from twenty-four healthy adult non-smokers. Blood viscosity and elasticity were determined using the Vilastic Scientific Bioprofiler for different concentrations (0, 2.5, 25, 50 and 100 ng/ml) of CBD and THC respectively, as well as in extracts with combinations of CBD and THC in 4:1 and 1:1 ratios respectively. Repeated measures analysis of variance (ANOVA) was used to determine the difference between the means of the groups. Results Blood viscosity increased significantly with increasing concentrations of both THC and CBD from 25 ng/ml up to 100 ng/ml ranging from 6.45 ± 0.36 mPa·s to 11.60 ± 1.12 mPa·s for THC and ranging from 5.46 ± 0.24 mPa·s to 9.91 ± 1.10 mPa·s for CBD respectively, being more pronounced in the extracts at 21.33 ± 2.17 mPa·s for the 4THC:1CBD extract and 21.76 ± 1.88 mPa·s for the 1THC:1CBD extract. There was no significant increase in elasticity for THC and CBD separately. However, a significant increase in elasticity was observed in the extracts. THC and CBD affected red cell morphology resulting in complete disintegration at the highest concentrations. Conclusions THC and CBD increased red blood cell viscosity and elasticity separately and in combination. They also adversely affected membrane integrity.